Adoption of Digital Payment System among the Youths in Pokhara Metropolitan City - Poudel, Hem Kanta; Ranabhat, Deepesh; Sapkota, Pradeep; Ranabhat, Mala (Journal of Innovation in Academia, 2023)
Effective payment systems are crucial components of any nation’s financial infrastructure. In recent years, Nepal has witnessed a significant surge in the utilization of digital payment systems. The examination of the adoption of digital payment methods in Nepal is of paramount importance as it sheds light on behaviors related to financial technology that can shape the future of the country’s financial system and contribute to its economic development. This study aims to explore the factors influencing the adoption intention of digital payment systems in Pokhara Metropolitan City, Nepal. The study population consists of the youth of Pokhara, with 400 respondents selected using a purposive sampling technique. Data analysis encompasses frequency distribution, exploratory factor analysis, and structural equation modeling. The exploratory factor analysis extracted six factors, which include effort expectancy, performance expectancy, security and privacy, social influence, facilitating conditions, and adoption intention. The structural equation modeling reveals that security and privacy, performance expectancy, and facilitating conditions have a significant positive impact on the adoption intention, whereas effort expectancy and social influence do not significantly affect the adoption intention of digital payments. In conclusion, the study suggests that the use of digital payment systems can be increased by providing secure digital payment systems, enhancing access to resources that support digital payments, and raising awareness about the benefits of digital payments among the youth in Pokhara Metropolitan City. These findings can guide policymakers in developing strategies and policies to promote the adoption of digital payments.